Advances in the development of cyclodextrin-based nanogels/microgels for biomedical applications: Drug delivery and beyond. (1st December 2022) - Topuz, Fuat; Uyar, Tamer
Abstract: Nanogels/microgels are swollen cross-linked polymer networks with tunable physicochemical properties and are commonly employed for the effective delivery of hydrophilic drugs. By structural engineering, they can be adapted for the delivery of hydrophobic drugs. Likewise, the use of cyclodextrins (CDs) as pharmaceutical excipients in nanogels drastically boosts the loading capacity of lipophilic drugs while enhancing their stability, bioavailability, and permeability owing to their capability of hosting drugs in their somewhat lipophilic cavity. Here, the synthesis and biomedical applications of CD-based nanogels/microgels were compiled with regard to the CD's role in nanogel synthesis. Even though most applications focused on using CD molecules as functional motifs to carry drugs and construct nanogels for biomedical applications, others used CDs in engineering nanogels to benefit from their supramolecular complexation ability. The applications of CD-based nanogels for drug-mediated cancer/tumor therapy were also discussed. Finally, the review points to the challenges/horizons to boost their biomedical applications. Graphical abstract: Unlabelled Image